ACUTE EFFECTS OF DIFFERENT STATIC STRETCHING PROTOCOLS ON PEAK TORQUE, CONVENTIONAL AND FUNCTIONAL HAMSTRINGS-TO-QUADRICEPS RATIOS IN ACTIVE WOMEN (International Journal of Physiotherapy, 2016)
Background: This study might have been directed to some degree because of clashing results in the past studies regarding the impacts for different SS protocols on muscle strength and possibility for injury. The objective of the study was to investigate the acute effects of different static stretching (SS) durations (20, 30, and 60s) on isokinetic concentric quadriceps (Q) and hamstrings (H) peak torque (PT), eccentric H PT and conventional and functional H:Q ratios under different stretching conditions and angular velocities (60°and180°/s) in active women.Methods: Isokinetic tests were performed on 108 active women. A HUMAC system was used to measure unilateral concentric Q and H PT, and eccentric H PT at 60 and 180º/s at baseline and after a bout of H-only, Q-only, and combined H and Q muscles SS. The data were statistically treated using five separate three-way (time x conditions x velocity) ANOVA.Results: There were no significant differences among groups at baseline (P > 0.05). Significant reductions of all outcome measures have been shown to occur after 30 and 60s of SS (P < 0.05). The highest reductions of concentric Q and H PT, eccentric H PT and H:Q ratios were observed after 60s of SS. With no significant effects with the 20s SS (P > 0.05).Conclusion: Short-lasting stretching can be done before exercises that require strength. However, since 30s or 60s stretching protocols adversely affect the muscle strength, performance and lower H:Q ratios they are not recommended prior to activities demanding the production of high forces.